The Role of NOD-like Receptors in Recognition of Pathogen-associated Molecular Patterns of Infectious Pathogens and in Development of Inflammation. Part 4. NLR Family Proteins are Involved in the Regulation of Process of Inflammation and Immune Respo - A.Ye. Abaturov; A.P. Volosovets; Ye.I. Yulish (Zaslavsky O.Yu., 2013)
The survey described mechanisms for participation of NLR family proteins in the regulation of process of inflammation and immune response.